The value of interleukin-12B (p40) gene promoter polymorphism in patients with schizophrenia in a region of East Turkey - Ozbey, Ulku; Tug, Esra; Kara, Murat; Namli, Mustafa (Wiley-Blackwell, 2008)
Aims: It has been hypothesized that the activation of the immune system may be involved in the neuropathological changes occurring in the central nervous system of schizophrenic patients. Cytokines play a key role in the activation of the immune system. Moreover, they strongly influence the dopaminergic, noradrenergic and serotonergic neurotransmission. To the best of our knowledge, in schizophrenic patients, plasma levels of interleukin (IL)-12 were investigated only in one study, where deregulation of IL-12 was determined. However, genotypical variations of the IL-12B (p40) gene have not been investigated for schizophrenic patients yet. Therefore, in the present study, we aimed to examine polymorphic variants of IL-12B (p40) gene promoter region in patients with schizophrenia in a population of the Elazig Region of East Anatolia, Turkey. Methods: One hundred Turkish patients diagnosed with schizophrenia based on the Diagnostic and Statistical Manual of Mental Disorders (DSM-IV), and 116 healthy control subjects participated in the present study. The genotype characteristics were determined by polymerase chain reaction-based restriction fragment length polymorphism method using DNA extracted from peripheral blood. Results: Significant differences in both the genotype and allele frequencies were found between schizophrenia patients and control groups (P < 0.01). Conclusions: These findings may support the hypothesis that activation of the inflammatory response system and in particular, of Th-1 cells, is involved in the pathophysiology of schizophrenia. We think that this study is the first trial associated with IL-12 cytokine at the molecular genetic level on immune mechanisms for neuropsychiatric disorders including schizophrenia, and this perspective and the role of the cytokines in the pathogenesis of schizophrenia may constitute a reasonable target for the present and future treatment strategies and prognosis.
Keywords: cytokines; interleukin-12B (p40) gene polymorphism; neuropsychiatric disorders; schizophrenia